Distinct Assembly Mechanisms Underlie Similar Biogeographic Patterns of Rare and Abundant Bacterioplankton in Cascade Reservoirs of a Large River - Chen, Juan; Wang, Peifang; Wang, Chao; Wang, Xun; Miao, Lingzhan; Liu, Sheng; Yuan, Qiusheng; Sun, Shenghao (Frontiers in Microbiology, 2020)
Bacterioplankton communities commonly consist of few highly abundant species and a large number of rare species that play key roles in biogeochemical cycles of aquatic ecosystems. However, little is known about the biogeographic assemblies of these communities, especially in large rivers suffering from cascade dam regulation. Here, we used a 16S rRNA gene amplicon sequencing approach to investigate the biogeographic patterns and underlying assembly mechanisms of abundant and rare bacterioplankton taxa in cascade reservoirs of the Jinsha River in China. The results revealed species loss of bacterioplankton due to dam construction, which was more significant for rare taxa than for abundant ones. The distributions of abundant and rare taxa exhibited similar spatial and temporal patterns, which were significantly distinct between winter and summer and between upstream and downstream reservoirs. Both spatial (dispersal-related process) and environmental (selection process) factors seemed to together govern the assembly and biogeography of abundant and rare taxa, although both factors explained only a small fraction of variation in the rare taxa. More importantly, environmental factors explained more community variation in abundant sub-community than that in rare sub-community. Co-occurrence network analysis revealed that abundant species with closer interactions were more often located in a central position of the network compared with rare species. Nevertheless, half of the keystone species were rare species, and may play important roles in maintaining the network stability. Overall, these findings indicate that distinct assembly mechanisms underlie the similar biogeography of rare and abundant bacteria in cascade reservoirs of a large river.